Determining the satisfaction level on safety aspects from visitors perspective in I-City Theme Park / Nik Nurul Nisrina Nik Yusoff - Nik Nurul Nisrina, Nik Yusoff (2018)
Theme park is one of the tourism products in Malaysia that generate the income to the country and influence the growth of tourism economy. Theme park in Malaysia has been the selected as the prior destination among the residents and tourist as it is one of famous attraction product for the purpose of leisure, recreational, entertainment and enjoyable activities besides providing tourist experience at the destination. The safety in theme park is very important factors and not just to make sure visitor’s safe from any injuries or incidents in theme park. Beside that in order to avoid problems in theme park, theme park visitors must be aware of the significance of reading the warnings, guidelines and guarantee that the ride regulations are seen. The aim of this research is to identify the level of visitor’s satisfaction in theme park. The purposes of this study is to identify the safety aspects in theme park, to identify the level of visitor’s satisfaction in theme park and to recommend the solution to improve safety in theme park. The scope of this research is focusing on the safety in theme park from visitor’s satisfaction in theme park I-City SHAH ALAM. A total of 50 questionnaires was distributed to I-City theme park in SHAH ALAM. Out of 50 questionnaires distributed, and all questionnaire were return back by the respondents. The collected data were transferred to SPSS software which the outcome has been in the form of table and bar chart. The result from the survey showed that the level of safety aspects in theme park were between moderate to high. Based on data analysis, it can be observed that visitor’s in theme park are very satisfied with facilities provided. The second strongly agree with to improve safety in theme park.